Relationship Between Distance Run Per Week, Omega-3 Index, and Arachidonic Acid (AA)/Eicosapentaenoic Acid (EPA) Ratio: An Observational Retrospective Study in Non-elite Runners - Davinelli, Sergio; Corbi, Graziamaria; Righetti, Stefano; Casiraghi, Elena; Chiappero, Francesco; Martegani, Serena; Pina, Riccardo; De Vivo, Immaculata; Simopoulos, Artemis P.; Scapagnini, Giovanni (Frontiers in Physiology, 2019)
Background: Tissue availability of polyunsaturated fatty acids (PUFA) depends on several factors, including dietary intake, physical exercise, genetic variation and metabolic turnover. However, there is limited evidence whether running training activity per se may influence indices associated with PUFA metabolism such as Omega-3 (ω-3) index and arachidonic acid (AA; 20:4ω-6)/eicosapentaenoic acid (EPA; 20:5ω-3) ratio. Objective: To examine the association between kilometres (Km) run per week and changes in ω-3 index and AA/EPA ratio. Methods: We conducted a retrospective, observational, cohort study of 257 non-elite runners (mean age: 40.85 ± 12.17 years) who consumed no fatty acid supplements and provided a blood sample for analysis. The whole blood samples were collected by finger sticks, stored on absorbent filter paper, and then PUFA were quantified by gas chromatography (GC) and ω-3 index and AA/EPA ratio measured. Results: In a multivariate linear regression model, a gradual decrease of the ω-3 index was observed with higher weekly running distance (β= -0.033; 95% CI -0.039 to -0.026; R2= 0.447; p<0.0001). We also found a progressive increase of the AA/EPA ratio in subjects who ran greater weekly distances (β= 0.092; 95% CI 0.038 to 0.146; R2= 0.320; p= 0.001). No other significant associations were observed with other variables, including years of running training and weekly training frequency (hours/week). Finally, as expected, a significant inverse correlation between ω-3 index and AA/EPA ratio (β= -2.614; 95% CI -3.407 to -1.821; R2= 0.336; p<0.0001) was detected. Conclusions: These findings suggest that distance running training and its weekly volume may negatively contribute to changes of the ω-3 index and AA/EPA ratio. Further studies with greater sample size will be required to replicate and extend these data.